Practices of strength and conditioning coaches in professional sports: a systematic review - Weldon, Anthony; Duncan, Michael J.; Turner, Anthony; Lockie, Robert G.; Loturco, Irineu (Biology of Sport, 2022)
The practices of strength and conditioning (S&C) coaches have been reported in various professional sports. This study aims to comprehensively assess this available evidence to help establish whether theoretical, practical, and evidence-based guidelines align with the practices employed by these experienced S&C coaches. Three databases were searched (PubMed, SPORTDiscus, and Cochrane) until November 2020. Studies surveying the practices of S&C coaches in professional sports using a survey design with common questions, written in English, and published in peer-reviewed journals were reviewed. Eight studies (n = 318 S&C coaches) were finally included. All studies adapted a similar survey, providing a strong basis for comparison between sports. Periodization strategies were widely used (89%), with training volume consistently reduced during the in-season period. Olympic weightlifting was commonly used across sports, except in baseball (29%). Plyometric exercises were predominantly prescribed for speed development (74%) and lower body power (68%), which were mostly programed as complex training (45%) and conducted all year round (52%). Flexibility exercises were mostly performed before practice (83%) for 6–10 min (40%). Physical tests were mainly conducted during the preseason period (66%), with body composition (86%) being the most used test. S&C coaches generally adhered to current guidelines and research in S&C concerning training prescription and physical testing. Whereas, intersport differences were also noted and further discussed. Results of this study can be used by S&C coaches to plan, implement, and review their professional practices. Furthermore, may inform the development of general and sport-specific guidelines, and future research in S&C.